Does the Ethno-Physics-based Problem Based Learning Model Improve Students' 21st Century Thinking Skills? Meta-analysis - Adwitya Rezky Septyan; Heru Kuswanto (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to determine the effectiveness of ethno-physics-based project-based learning model to improve students' 21st century thinking skills.  Inclusion criteria in this study are research published in 2022-2024, research must be experimental or quasi-experimental methods, research obtained through Google Scholar, ScienceDirect, Wiley, ERIC, ProQuest, Fronteins and Web of Science databases, research must be relevant and consist of 1229 students. Data analysis in this meta-analysis with the help of JSAP application. The analysis of 24 studies concluded that the resulting random effect size value was 1.05 (high effect size category) with 95% confidence level.  This finding explains that the ethno-physics-based project-based learning model can improve students' 21st century thinking skills. This research can also provide new information related to the application of problem-based learning model in the future.